2008
DOI: 10.3354/ame01186
|View full text |Cite
|
Sign up to set email alerts
|

Habitat partitioning of denitrifying bacterial communities carrying nirS or nirK genes in the stratified water column of Lake Kinneret, Israel

Abstract: The community composition of denitrifying bacteria was studied in the stratified water column of Lake Kinneret. The nitrite reductase genes nirS and nirK were amplified by PCR from water samples taken at 1, 14, 19 and 22 m depth, which represent the epi-, meta-and hypolimnion of the lake. The PCR products were analyzed with terminal restriction fragment length polymorphism (T-RFLP) and clone libraries. The highest diversity of nirS denitrifying communities was observed at 1 m depth. According to the T-RFLP pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…The total abundance of nirK denitrifiers may also vary spatially and temporally (Dandie et al 2008), and it has been reported to correlate with denitrification activity in stream sediments (O'Connor et al 2006). The nirS community was not addressed in the present study, due to technical problems in the nirS-DGGE, but it is possible that the response to environmental factors varies between nirK and nirS communities (Desnues et al 2007, Junier et al 2008, Enwall et al 2010, Kim et al 2011. A more complete picture of the denitrifier community could be acquired by concurrent analyses of nirS-containing communities and the total abundance of denitrification genes by qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The total abundance of nirK denitrifiers may also vary spatially and temporally (Dandie et al 2008), and it has been reported to correlate with denitrification activity in stream sediments (O'Connor et al 2006). The nirS community was not addressed in the present study, due to technical problems in the nirS-DGGE, but it is possible that the response to environmental factors varies between nirK and nirS communities (Desnues et al 2007, Junier et al 2008, Enwall et al 2010, Kim et al 2011. A more complete picture of the denitrifier community could be acquired by concurrent analyses of nirS-containing communities and the total abundance of denitrification genes by qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study on the community composition of denitrifying bacteria in Lake Kinneret (Israel), we have found that denitrifying bacteria carrying the nirK and nirS genes are differentially distributed in the stratified water column. In Lake Kinneret, communities of nirS-denitrifiers were diversified in the epilimnion and nirK-denitrifiers in the anoxic hypolimnion (Junier et al 2008b). …”
Section: Introductionmentioning
confidence: 97%
“…However, 14 C bicarbonate uptake experiments that have been carried out for many years and in different seasons suggest that at the chemocline in autumn, when the oxycline and the thermocline are at the same depth within a narrow metalimnetic layer below the euphotic zone, sulfide oxidation is a much more significant process than ammonia oxidation (Hadas et al 2001). Although ammonia oxidation exists, and may be coupled to denitrification, as shown by amplification of the nitrite reductase gene nirS in the same samples (Junier et al 2008c), it is negligible during this period. In the lower part of the gradient, ammonia concentrations decrease from 14.2 µmol l -1 at 17.7 m to 6.3 µmol l -1 at 16.6 m depth, without the accumulation of nitrate and in the absence of amoA sequences in the libraries suggesting assimilation processes by metalimnetic biota rather than ammonia oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…T-RFLP data were analyzed using GeneScan 3.1 software (Applied Biosystems). Data analysis was carried out as described in Junier et al (2008c). Simulations of terminal restriction fragments (T-RFs) from clonal sequences from this study were carried out using TRiFLe (Junier et al 2008a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation